Analisis Yuridis Asas Kepentingan Terbaik bagi Anak dalam Pemidanaan Anak Pelaku Pengedar Narkotika - Rudi Pujianto; Silvia Nur Faizah; Novi Nour Hidayati; Gale Adhyasta Adikara (Jurnal Hukum Lex Generalis, 2025)
This study analyzes the application of the best interests of the child principle in sentencing children involved as narcotics distributors in Indonesia. It employs a normative juridical method with statutory and conceptual approaches. The findings reveal a lack of harmonization between the repressive orientation of the Narcotics Law and the protective framework of the Child Protection Law and the Juvenile Criminal Justice System Law, which prioritize guidance and rehabilitation. Nevertheless, judicial decisions have begun to develop a more protective interpretation by recognizing children as vulnerable subjects often exploited by narcotics networks. This study recommends the formulation of specific sentencing guidelines for juveniles, the optimization of diversion mechanisms and the strengthening of rehabilitation and guidance through specialized child-focused institutions.